Effects of Micronucleus Frequencies and Mitochondrial DNA Copy Numbers among Benzene‐Exposed Workers in China. (10th January 2020) - Li, Anqi; Sun, Yuan; Wang, Tongshuai; Wang, Kan; Wang, Tuanwei; Liu, Wuzhong; Li, Keyong; Au, William W.; Wang, Zubing; Xia, Zhao‐lin
Abstract : To provide a more comprehensive understanding of genotoxic effects from benzene exposure, its effects on induction of mitochondrial DNA copy number (MtDNAcn) and of micronucleus (MN) were investigated using peripheral blood from workers in China. Changes in mtDNAcn and MN were determined using quantitative real‐time polymerase chain reaction (PCR) and cytokinesis‐block micronucleus assays (CBMN), respectively, in 58 control and 174 benzene‐exposed workers in Shanghai, China. Among the exposed workers, relative mtDNAcn increased and then decreased with increasing doses of benzene exposure. Significant and dose‐dependent increase in MN frequencies were observed among the different exposure groups. In addition, the relative mtDNAcn were significantly associated with the MN frequencies in the low‐level exposure group ( P = 0.046), but not in the high dose groups. Therefore, the mechanisms for induction of MtDNAcn and MN by benzene may be similar from exposure to low doses but different from high doses. Similar increase of MN frequencies and MtDNAcn may be due to oxidative stress induced by benzene at low concentrations, while higher concentrations may start to initiate the cell death pathway. The pathway may be associated with excessive MtDNAcn which can initiate apoptosis while MN can continue to be induced. However, the differential mechanisms need to be investigated because they may represent different levels of risk for different health consequences. On the other hand, our data indicate that induction of MtDNAcn may be a sensitive genotoxic biomarker for workers with exposure to low dose of benzene. Environ. Mol. Mutagen. 61:355–360, 2020. © 2020 Wiley Periodicals, Inc.